A MANAJEMEN BIRO PENGASUHAN DALAM MEMBENTUK DISIPLIN DAN AKHLAKUL KARIMAH SANTRI DI PONDOK PESANTREN: MANAJEMEN BIRO PENGASUHAN DALAM MEMBENTUK DISIPLIN DAN AKHLAKUL KARIMAH SANTRI DI PONDOK PESANTREN - Fatimah (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2023)
This type of research is a case study as a deeper research on individuals, a group, an organization, activity plans, and others at various specified times. With the aim of obtaining a definite and deeper explanation of an entity. Case studies obtain information and then analyze to obtain theory. Moral education at the Integrated Nurul Islam Blang Rakal Islamic Boarding School is expected to be able to give birth to generations who are moral and have the personality of the Qur'an with religious values which are the forerunners of nation building with a religious identity attached to them. The results of the study can be concluded that the management of the parenting bureau in forming discipline and akhlakul karimah in the integrated Nurul Islam Islamic Boarding School takes several steps including: 1). The Nurul Islam Blang Rakal Islamic Boarding School has a special plan to foster the morals of students, by teaching students about religious values and providing examples of a teacher's example so that they can be seen and imitated in everyday life. 2). Facilitating the equipment needed by participants during their education at Islamic boarding schools in connection with the formation of the required akhlakul karimah. Keywords : Akhlakul Karimah, Caregiver Bureau, Islamic Boarding School, Discipline